Neurofibromatosis type 1 in childhood: correlation of MRI findings with intelligence. Issue 6 (December 1995) - Legius, E; Descheemaeker, M J; Steyaert, J; Spaepen, A; Vlietinck, R; Casaer, P; Demaerel, P; Fryns, J P
Abstract : In a group of 28 children with neurofibromatosis type 1 aged between 4 and 16 years, neuroradiological findings were correlated with intelligence as measured by the Wechsler scales. The presence or specific location in the brain of T2 weighted prolonged signals on MRI was not associated with cognitive problems. No other physical characteristics associated with neurofibromatosis type 1 were found to correlate significantly with IQ. At the present these T2 weighted hyper-intense spots should not be used to predict neurofibromatosis type 1 associated cognitive problems.